Vaporisation of Single and Binary Component Droplets in Heated Flowing Gas Stream and on Solid Sphere - Nguyen Thi Bang Tuyen
Chapter 1.Introduction; Chapter 2.Literature review; Chapter 3.Comparison of vaporization models for feed droplet in fluid catalytic cracking risers; ...